2021
DOI: 10.1002/jqs.3273
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the extent to which fluctuations in ice‐rafted debris reflect mass changes in the source ice sheet: a model–observation comparison using the last British–Irish Ice Sheet

Abstract: The British and Irish Ice Sheet (BIIS) was highly dynamic during the Late Quaternary, with considerable regional differences in the timing and extent of its change. This was reflected in equally variable offshore ice‐rafted debris (IRD) records. Here we reconcile these two records using the FRUGAL intermediate complexity iceberg–climate model, with varying BIIS catchment‐level iceberg fluxes, to simulate change in IRD origin and magnitude along the western European margin at 1000‐year time steps during the hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…States (Condron & Hill, 2021;Hill & Condron, 2014) or the transport of sediment from the British Irish Ice Sheet (Wilton et al, 2021), rather than the more extensive region of IRD found across the IRD belt in the North Atlantic. Using a model with a fine scale (1/6°; 18-km) ocean, this work investigates the sensitivity of patterns of iceberg tracks to both iceberg size and to changes in climatic (environmental) factors.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…States (Condron & Hill, 2021;Hill & Condron, 2014) or the transport of sediment from the British Irish Ice Sheet (Wilton et al, 2021), rather than the more extensive region of IRD found across the IRD belt in the North Atlantic. Using a model with a fine scale (1/6°; 18-km) ocean, this work investigates the sensitivity of patterns of iceberg tracks to both iceberg size and to changes in climatic (environmental) factors.…”
Section: Introductionmentioning
confidence: 97%
“…Finer scale modeling is however necessary to more accurately resolve individual iceberg tracks and precisely where IRD was deposited during Heinrich Events. To‐date, previous modeling efforts using finer scale grids have tended to focus on the transport of icebergs and fresh water along the Eastern seaboard of the United States (Condron & Hill, 2021; Hill & Condron, 2014) or the transport of sediment from the British Irish Ice Sheet (Wilton et al., 2021), rather than the more extensive region of IRD found across the IRD belt in the North Atlantic. Using a model with a fine scale (1/6°; 18‐km) ocean, this work investigates the sensitivity of patterns of iceberg tracks to both iceberg size and to changes in climatic (environmental) factors.…”
Section: Introductionmentioning
confidence: 99%
“…Wilton et al . (2021) explored this comparing by results from an iceberg–ocean model tracking the trajectory of icebergs discharged from the ice sheet (using fluxes from the ice‐sheet modelling), and computing the likely fluxes of debris delivered to nearby observations of ice rafted debris.…”
Section: Discussionmentioning
confidence: 99%
“…These results on the timing and pacing of ice withdrawal are then used to understand the main controls that drove or modulated ice sheet retreat (Benetti et al ., 2021; Bradwell et al ., 2021a,b; Chiverrell et al ., 2021; Evans et al ., 2021; Ó Cofaigh et al ., 2021; Scourse et al ., 2021). A further paper reports on how ice sheet modelling experiments and empirical data can be used in combination (Ely et al ., 2021), and another probes the glaciological meaning of ice‐rafted debris (Wilton et al ., 2021).…”
Section: The Britice‐chrono Projectmentioning
confidence: 99%
“…Ice discharge fluxes derived from the PISM ice sheet modelling have been used to seed and drive modelling of iceberg trajectories (using the model of Levine and Bigg, 2008) in the North Atlantic. This was to address questions of how ice sheet mass balance relates to variations in ice‐rafted debris (Wilton et al ., 2021). The higher‐order adapative mesh model, BISICLES (Conford et al ., 2013), which permits fine‐scale resolution grids near ice streams, for example, has been applied to address three important questions, all making direct comparisons with BRITICE‐CHRONO data.…”
Section: A Data‐rich Environment To Improve Ice Sheet and Glacio‐isostatic Adjustment Modellingmentioning
confidence: 99%